Вы находитесь на странице: 1из 5

" "

..
1. ,
.
: {X(t), t 0}
{Y (t) = X(t) X(0), t 0}. , {Y (t), t 0} . E(Y (t)) = a(t). ,
,
a(t + s) = a(t) + a(s), t, s 0

(1)

, (1) a(t) = ct1 .


, t = 1. , E(Y (t)) = tE(Y (1)).
.
{Y (t), t
2
0} . , t s.
cov(Y (t), Y (s)) = E(Y (t)Y (s)) E(Y (t))E(Y (s)) =
= E((Y (t)Y (s)+Y (s))Y (s))E(Y (t))E(Y (s)) = E(Y (t)Y (s))E(Y (s))+
+ E(Y (s))2 E(Y (t))E(Y (s)) = E(Y (s))2 (E(Y (s)))2 = D(Y (s))

.
2. (t) = A cos(t + ), , A , E(A) = m, D(A) = 2 , [0, 2]3 . ,
(t). ,
.
: :
E((t)) = E(A)E(cos(t + )) = 0, .
1


.

3 -,
2

:
K(t, s) = cov((t), (s)) = E((t)(s)) E((t))E((s)) = E((t)(s)) =
m2 + 2
2
= E(A )E(cos(t + ) cos(s + )) =
cos((t s))
2
.
,
s = t.
.
3. W (t) . ,
, .
: . R
4. (t) , (t) = 0t (s)ds , (t).
: {(t), t 0}
. ,
E|(t + s) (t)|2 = E|(s)|2 = 2 s2 + s 0, s 0
,
[t s]:
E((t)) =

Z t

E((s))ds =

cov((t), (s)) =

Z tZ s
0

K (u, v)dudv =

Z tZ s
0

t2
;
2

min(u, v)dudv =

s2
[3t s];
6

t3
.
3
R
5. R W (t) , 1 = 0 cos(t)dW (t),
2 = 0 sin(t)dW (t). : E(1 ), E(2 ), D(1 ), D(2 ), cov(1 , 2 ).
: ,
D((t)) =

E(1 ) = E(2 ) = 0;
D(1 ) = E(1 )2 =

Z
0

cos2 (t)dt =

, D(2 ) = E(2 )2 =
sin2 (t)dt = ;
2
2
0

cov(1 , 2 ) = E(1 2 ) =

Z
0

sin(t) cos(t)dt = 0.

6.
R( ) = exp( 2 ). f (). ,
f () = exp(||), K( ).
: .
2
1
2
f () = e 4 , K( ) = 2
2
+1

,

.
7.
W (t) , h( ) = exp( ), >
Rt
0, (t) =
h(t s)W (s)ds. ,
.
Rt
h(t s)dW (s).
(t) =
: , ,
.


. 3
, [t1 t2 ]
E((t)) =

Z +

E(h(t s)W (s))ds = 0;

Z t1

cov((t1 ), (t2 )) = cov

h(t1 s1 )W (s1 )ds1 ,

Z t2

Z t1

= exp((t1 + t2 ))cov

exp(s1 )W (s1 )ds1 ,

= exp((t1 + t2 ))
= exp((t1 + t2 ))

Z t1 Z t2

Z t1 Z t2

h(t2 s2 )W (s2 )ds2 =

Z t2

exp(s2 )W (s2 )ds2 =

exp(s1 + s2 )KW (s1 , s2 )ds1 ds2 =


exp(s1 + s2 ) min(s1 , s2 )ds1 ds2 =
1
= t1 1 et1 t2 ;
2

3
D((t)) = t ;
2
E((t)) = 0;
cov((t1 ), (t2 )) =

Z +

1
h(t1 s)h(t2 s)ds = et1 t2 ;
2

1
D((t)) = .
2
3

8.
L = {1 1 + 2 2 }, 1 , 2 , 1 , 2 R1 , E(1 ) = E(2 ) = E() =
0, D(1 ) = D() = 1, D(2 ) = 4, cov(1 , 2 ) = 1, cov(1 , ) = 0.5, cov(2 , ) =
1.
: , b L,
( b, ) = 0 L
(2)
b 1 1 +
b 2 2 , = 1 1 + 2 2 . (2)
b =
4 :
b 1 1
b 2 2 )(1 1 + 2 2 )] =
( b, ) = E[( b)] = E[(
b 2 E(1 2 )
b 2 2 E(2 )2 =
b 1 1 E(1 )2
b 1 2 E(1 2 )1
= 1 E(1 )+2 E(2 )
b 1 1 +
b 1 2 + 1
b 2 4
b 2 2
= 0.51 + 2

(1 , 2 ) (1, 0), (0, 1),


:
(
b 1 4
b 2 = 0;
1+
b1 +
b 2 = 0.
0.5
b 1 = 1,
b 2 = 0.5. ,

: b = 1 + 0.52 .
9. (n) f () = 10 + 6 cos() = |3 + ei |2 . (n), n 0,
.
:
:
1) f () = |f1 ()|2 ,
f1 () = 3 + ei L0 ;
2) h1 f1 () = ei (3 + ei ) = 1 + 3ei ;
3) h1 f1 () = k1 + k2 , k1 = 1 L0 , k2 = 3ei L>0 ;
P
4) g() = n0 cbn ein g()f1 () = k1 .
.
5)
b
(1)
=

cbn n =

n0

(3)n1 (n)

n0

10. (t)
d(t) = et (t)dt + d(t), t 0.
4 , ,

.
: , ,
:
(t) = W (t, 0)(0) +

Z t

W (t, s)d(s),

W (t, s) :
(

d
W (t, s)
dt

= et W (t, s), t > s;


W (s, s) = 1.

W (t, s), :
t

(t) = exp(1 e )(0) +

Z t

exp(es et )d(s)

11, 12. ,
.
13. (t) f () = exp(||). ,
.
R +
||2 f ()d < : ,
5 . ,
, .
,
: f1 () = |()|2 f (), () , i. ,
f1 () = 2 e|| . .

4[3t2 1]
K1 (t) = 2
(t + 1)3
14. (t) . (t) + 0 (t). ,
.
: . , , () = 1 + i.
5